Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Handphone Merek Samsung (Studi Kasus Pada Mahasiswa Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Victory Sorong) - Samuel Yohanes Warella; Susana Magdalena Welly Muskita (ARBITRASE: Journal of Economics and Accounting, 2020)
In the current era of globalization, human needs for information increase along with the times. To get this information, among others, can be done by exploring the virtual world that is using the internet, to expand the horizon, can be obtained through communication using mobile phones or mobile phones. The results of open interviews with students of the management study program at the Faculty of Economics and Business at Victory Sorong University on several smartphone brands that are used by students show that Samsung is a brand that is more dominating and more desirable. The purpose of this study was to determine how much influence the quality of the product on the purchasing decision of Samsung brand mobile phones on students of the Management Study Program at the Faculty of Economics and Business, University of Victory Sorong. The population and sample used were students of the Management Study Program at the Faculty of Economics and Business, University of Victory Sorong who used 58 Samsung brand mobile phones. The results of a simple linear regression analysis showed a positive influence between product quality in improving purchasing decisions obtained Y = 2.835 + 0.327 X + e The equation shows that product quality is affected by purchasing decisions. Partial test results (t test), produced t-product quality t-test 3080> t-table 1.6725, meaning significant. Significant here means that the Hypothesis is accepted. That is, because t-count> t-table, it can be concluded that there is a positive influence between "product quality on purchasing decisions of Samsung brand mobile phones on students of Management Studies Program at the Faculty of Economics and Business, University of Victory Sorong, the hypothesis is accepted